Core Java - Horstmann, Cay S. (Pearson, 2019)
This is the definitive guide to writing robust, maintainable code with the Java SE 9, 10, and 11 language and libraries. Horstmann writes for serious programmers who use Java in production projects, and need a deep, practical understanding of the language and API. Throughout, he delivers what you need most: hundreds of real (non-toy) examples revealing the most powerful, effective ways to get the job done. Updated examples reflect the new var keyword and take advantage of improvements in the Java API. You'll learn how to use JShell's new Read-Eval-Print Loop (REPL) for more rapid and exploratory development, and apply new features of the APIs for streams, input/output, processes, and concurrency.